Analisis Faktor-Faktor yang Mempengaruhi Kualitas Informasi Akuntansi (pada Organisasi Perangkat Daerah (OPD) di Gunungkidul) - Utami, Putri; Adhivinna, Vidya Vitta (AKMENIKA, 2018)
Accounting information is very important thing in business activities or government. Accounting information is used as decision making in organization. The purpose this research to analyze affect relevant information, reliable information, complete information, timely information, understandable information toward quality accounting information at Organisasi Perangkat Daerah (OPD) in Gunungkidul.This Research is quantitative research with purposive random sampling technique. Employee population 11 Dinas that use Accounting Information, the sample of wich was obtained 68 people. The analysis technique used is multiple regression analysis.The result of the research shows that partially relevant information valuable 0,000 and complete information valuable 0,000 smaller than 0,05 has an effect on quality accounting information, while reliable information valuable 0,351 , timely information valuable 0,574 and understandable information valuable 0,680 greather than 0,05 no effect on quality accounting information. But simultaneously relevant information, reliable information, timely information, complete information and understandable information affect the performance of accounting information valuable 0,000 greather 0,05.Keywords: relevant information, reliable information, complete information, timely information, understandable information, quality accounting information.